Emergence and initial growth of rambutan seedlings as a function of seed storage conditions - Lucena Cavalcante, Italo Herbert [UNESP]; Segeren, Adriano [UNESP]; Geraldo Martins, Antonio Baldo [UNESP] (Edp Sciences S A, 2008)
Introduction. Rambutan is a tropical fruit species with recalcitrant seeds. Despite the expansion of exotic fruit cultivation in Brazil, lots of which fruit species, including rambutan, need basic information, especially in relation to propagation and storage of seeds, which are important for genetic improvement studies, maintenance of genetic sources and seedling production. Materials and methods. A completely randomized design was adopted with treatments distributed in a factorial arrangement, 3 x 4, referring to three seed storage conditions [room temperature conditions; a dry chamber with (18 +/- 2) degrees C and 60% relative humidity; and a cold chamber with (10 +/- 2) degrees C and 70% relative humidity] and four storage times ( 0, 7, 14 and 21 d). Each treatment of 10 seeds was replicated five times. Data on seedling emergence, emergence rate, plant height, number of leaves and length of main root were submitted to variance analysis and means were separated using Tukey's test. Correlation analysis between seed moisture and seedling emergence was performed. Results and discussion. Our results indicated that dry chamber conditions promoted the statistically significantly highest seedling emergence after 7 d of storage. Cold chamber conditions promoted an extremely low seedling emergence independently of time. Conclusion. Rambutan seeds can be stored in a dry chamber for 7 d without losing viability; after 14 d of storage the loss of emergence is 60%.
Keywords: Brazil; Nephelium lappaceum; seeds; seed storage; emergence